Equity, access and democratization of higher education : Report of current policies and practices in Georgia - Tchkadua, Shalva; Khositashvili, Giga (PRATICA - Revista Multimédia de Investigação em Inovação Pedagógica e Práticas de e-Learning, 2022)
Georgian higher education system has been gone through different phases of reforms after the country regained its independence in 1991. In this report the major directions of the GE Higher Education are explained – with an eye to the equity, access and democratization. Although there are different types of higher educational institutions each and every of them are going through the internal and external quality assurance measures before they are authorized by state. Students are enrolled at the university based on their scores in national exams, which was presented back in 2005. Higher education in general is not free, some students can get scholarships from state but the majority have to pay by themselves, thus affordability is an issue, especially on Masters and PhD levels. In addition to this, the majority of the students have to work at the same time of their studies, that is also an issue when speaking about the equity and accessibility.